Problematika Pengelolaan Pesantren Ramadhan tingkat SD dan SMP di Lubuk Buaya Kota Padang - wahyu fitrina defi (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
The month of Ramadan is the month of forgiveness and the month of Maghfirah. All useful activities carried out in this month will be rewarded with Him. Most schools in Indonesia, in the month of Ramadan, policies are often made to keep students in school by cutting time in the learning process. In contrast to one area of Padang, which makes a policy so that the learning process for students is transferred to the mosque/musholla during the month of Ramadan. However, in the implementation process, there are still a number of obstacles which can be detailed in the following four points: 1) Planning for the management of the Ramadan Islamic Boarding School, 2) Organizing the Ramadan Islamic Boarding School 3) Implementation of the Ramadan Islamic Boarding School, 4) Evaluation of the Ramadan Islamic Boarding School. The research method is qualitative research. The data collection technique was done by interview, observation, and documentation study. The data were analyzed with the stages of data reduction, data presentation, and drawing conclusions. Research informants were students, presenters, supervisors of Ramadhan Islamic boarding schools consisting of teachers and youth of mosques/musholla, and parents of students.